Addressing human rights abuses at mega-sporting events—A shared responsibility in theory and practice - Heerdt, Daniela (Frontiers in Sports and Active Living, 2023)
Mega-sporting events (MSEs) have great potential to promote human rights and be a force for good, not only in the host country or city where the event takes place, but also beyond. At the same time, these events are regularly linked to human rights abuses and this opinion piece provides an overview of MSE-related adverse human rights impacts and discusses how the governance of these events enables these impacts to occur in the context of bidding for, preparing, and delivering these events. At the core of this discussion the paper presents a shared responsibility approach and argues that if applied in a preventative and retrospective way and including the concept of collaborative remedy, it can help address these adverse impacts. This is followed by a reflection on the feasibility of this approach, by considering to what extent current developments in the evolving sport and human rights movement are going in that direction and the paper finishes with a brief discussion on the importance of making the current changes sustainable and how research and education are key elements of this endeavour.